Bimbingan Teknis Pembuatan Yoghurt Varian Rasa Dalam Rangka Pengentasan Stunting Di Dusun Kertaraharja Desa Gangga Kecamatan Gangga Kabupaten Lombok Utara - Dohi, Muhammad; Wandira, Ica Ayu; Haryanto, Haryanto; Sadia, I Nyoman (Jurnal Gema Ngabdi, 2024)
This community service activity focused on providing technical guidance on making flavored yogurt as a strategy to alleviate stunting in Kertaraharja Hamlet, Gangga Village, Gangga District, North Lombok Regency. The initiative aimed to educate the community on the importance of PE (Peranakan Etawa) goat's milk as a vital source of family nutrition to prevent stunting. The activity included a demonstration of the process of turning PE goat's milk into yogurt, with the goal of motivating the community to understand, adopt, and continue utilizing PE goat's milk as a nutritious food source for families, thereby increasing the economic value of PE goat's milk and boosting farmers' incomes. This activity was initiated in response to identified issues, such as the underutilization of PE goat's milk as a nutritional resource, the lack of experience among farmers in processing PE goat's milk into new products, and the generally low level of public awareness regarding the benefits of livestock milk. The expected outcomes include increasing public knowledge about the nutritional importance of PE goat's milk, enhancing community skills in processing milk from PE goats, extending the shelf life of the milk through processing, raising the market value of the milk, and fostering a healthy, prosperous, and self-reliant community in Gangga Village. Participants in this service activity was attended by 25 people included various community members from Gangga Village, such as breeders, village officials, and other residents. After the activity, the community gained a better understanding of the importance of utilizing and processing PE goat's milk into yogurt.